Biodiversity of the white coral bank off Cape Santa Maria di Leuca (Mediterranean Sea): An update - MASTROTOTARO, FRANCESCO; D'ONGHIA, Gianfranco; CORRIERO, Giuseppe; MATARRESE, Alfonso; MAIORANO, Porzia; TURSI, Angelo Raffaele; Panetta P; Gherardi M; LONGO, CATERINA; Rosso A; Sciuto F; Sanfilippo R; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2010)
The biodiversity of the Santa Maria di Leuca (SML) coral bank is summarized and its description is updated using data collected by means of underwater video systems, benthic samplers and fishing gears. A total of 222 living species have been recorded within the coral bank area in the depth range 280-1121 m. The most abundant benthic taxa recorded are Porifera (36 species) followed by Mollusca (35) and Cnidaria (31). The scleractinian corals Madrepora oculata and Lophelia pertusa are the main colonial species in the structure of the SML bank. Annelida, Crustacea and Bryozoa have been found with 24, 23 and 19 species, respectively. A total of 40 species of demersal fish have been recorded. Other faunal taxa were found with small numbers of species. One hundred and thirty-five species are new for the SML bank, 31 of which represent new records for the north-western Ionian Sea (2 Porifera, 17 Cnidaria, 1 Mollusca, 3 Annelida, 2 Crustacea, 4 Bryozoa and 4 Echinodermata). The finding of the annelid Harrnothoe vesiculosa represents the first record for the Mediterranean Sea. The SML coral bank represents a biodiversity "hot-spot" on the bathyal bottoms of the Mediterranean Sea. (C) 2009 Elsevier Ltd. All rights reserved.